Frequency and Amplification for Assessing site Effects and PVS in the Padang City Railway - Dwi Pujiastuti; Nadila Syarah; Nurul Annisa; Ahmad Fauzi Poha (Universitas Andalas, 2023)
The train uses a special line in the form of railroad tracks that produce vibrations during movement. This study aims to determine the type of soil layer and the peak particle velocity due to the train around the Padang City train line. The acquisition was carried out at 8 points with a recording duration of 65 minutes using three geophone components. Microtremor data was analyzed using horizontal to vertical spectral ratio (HVSR) method. The results show that the research area has a type of surface layer of soil is sediment with a thickness of 30 meters or more. This is indicated by the dominant frequency value ranging from 0.64 Hz – 1.67 Hz. The research area has an amplification value ranging from 0.85 to 1.29. The train vibration has a dominant frequency ranging from 2.20 Hz – 13.54 Hz and an amplification of 1.11 – 1.82. The particle velocity values ​​obtained from the PVS values ​​ranged from 0.1605 mm/s – 0.7592 mm/s. The research area can be categorized as safe from train vibrations because of the low amplification value and the PVS value which is below the safe limit (<3 mm/s) according to SNI 7571:2010.